Tumor necrosis factor induces rapid production of 1'2'diacylglycerol by a phosphatidylcholine-specific phospholipase C (The Rockefeller University Press, 1991)
Tumor necrosis factor (TNF) is a proinflammatory polypeptide that is able to induce a great diversity of cellular responses via modulating the expression of a number of different genes. One major pathway by which TNF receptors communicate signals from the membrane to the cell nucleus involves protein kinase C (PKC). In the present study, we have addressed the molecular mechanism of TNF-induced PKC activation. To this, membrane lipids of the human histiocytic cell line U937 were labeled by incubation with various radioactive precursors, and TNF- induced changes in phospholipid, neutral lipid, and water-soluble metabolites were analyzed by thin layer chromatography. TNF treatment of U937 cells resulted in a rapid and transient increase of 1'2'diacylglycerol (DAG), a well-known activator of PKC. The increase in DAG was detectable as early as 15 s after TNF treatment and peaked at 60 s. DAG increments were most pronounced (approximately 360% of basal levels) when cells were preincubated with [14C]lysophosphatidylcholine, which was predominantly incorporated into the phosphatidylcholine (PC) pool of the plasma-membranes. Further extensive examination of changes in metabolically labeled phospholipids indicated that TNF-stimulated hydrolysis of PC is accompanied by the generation of phosphorylcholine and DAG. These results suggest the operation of a PC-specific phospholipase C. Since no changes in phosphatidic acid (PA) and choline were observed and the production of DAG by TNF could not be blocked by either propranolol or ethanol, a combined activation of phospholipase D and PA-phosphohydrolase in DAG production appears unlikely. TNF-stimulated DAG production as well as PKC activation could be blocked by the phospholipase inhibitor p- bromophenacylbromide (BPB). Since BPB did not inactivate PKC directly, these findings underscore that TNF activates PKC via formation of DAG. TNF stimulation of DAG production could be inhibited by preincubation of cells with a monoclonal anti-TNF receptor (p55-60) antibody, indicating that activation of a PC-specific phospholipase C is a TNF receptor-mediated event.